PENGARUH CITRA MEREK, KUALITAS PRODUK DAN INOVASI PRODUK TERHADAP LOYALITAS KONSUMEN MOBIL AVANZA DI KABUPATEN PASAMAN BARAT - Mai Yuliza (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2017)
The purpose of this research is to know the influence of brand image, product qualityand product innovation toavanza car consumer loyalty in west pasaman regency. Population is the users of avanza cars in west pasaman regency with a sample of 100 peoples. Withconvinience sampling method. The research instrument is questionnaire, the data obtained then processed using multiple linear regression analysis technique using SPSS, from the results of this reserach found the brand image variable (X1), product quality (X2) and product innovation (X3) have a significant effect on loyalty (Y) with a significant level of 0.000. The magnitude of the influence of brand image (X1), product quality (X2) and product innovation (X3) have significant effect on loyalty (Y) is 0,729 (R2 = 72,9%). Keywords: Consumer Loyalty, Brand Image, Product Quality, Product Innovation